Global mixing indices for single screw extrusion - Domingues, N. (2008)
The present work presents numerical simulations of dispersive and distributive mixing of a two phase system being processed in a single screw extruder under various conditions. Models were developed to quantify the degree of mixing of liquid-liquid and solids-liquid systems, for a given set of material properties, operating conditions and extruder geometry.